Quaternion with quantum walks for designing a novel color image cryptosystem. (December 2022) - Abd-El-Atty, Bassem
Abstract: Data confidentiality plays a paramount part in our everyday lives. While most modern cryptosystems perform skillfully on digital resources, the rapid development of quantum resources may provide sufficient capability in the near future to hack most current cryptosystems because their construction is mathematical model-based. Although quantum algorithms will not be effective until quantum computers are physically realized and have sufficient capability to outperform digital computation, new cryptosystems are required to be designed using quantum technologies and have the capability to be implemented in both digital and quantum resources besides resisting the probable attacks from those resources. Quantum walk is a computational paradigm that can be implemented as a quantum-inspired paradigm and serves as a chaotic dynamical model employed for developing modern cryptosystems. This work presented a new color image cryptosystem using quaternion, quantum walks, and logistic-sine map. The aim of utilizing quaternion is to increase the key space of the presented cryptosystem, in addition to integrating the sequence originating from the logistic-sine map with the probability distribution originating from quantum walks for generating inseparable chaotic sequences utilized in the permutation and substitution phases of the presented image cryptosystem. Experimental outcomes were performed on 21 color images and the average values of UACI is 33.45969%, NPCR is 99.61070%, correlation is -0.00003, Chi-square is 255.904, global entropy is 7.999837, local entropy is 7.902542, and the encryption speed is 0.725868 Megabytes/second, in which the outcomes demonstrated that the offered encryption technique is both efficient and secure.